Role of Kisspeptin in Female Infertility (Pulse, 2016)
Background: Kiss1, a noble G protein coupled receptor designated as GPR54, was first identified in rat brain in 1999 and orthologue gene identified in human in 2001 the original niche for the function of kisspeptin was restricted to cancer biology for their ability to suppress tumor metastasis. However, kisspeptin has recently emerged as a key player in the field of reproductive endocrinology.Method: A systematic literature review was done by using PUBMED. Though there is lack of human data, used animal data also hold translational potential for human. Results: Inactivating mutation of GPR54 gene is linked with absence of puberty onset and idiopathic hypogonadotrophic hypogonadism. Furthermore, recent studies support critical role of kisspeptin/GPR54 system on regulation of GnRH neurons, involvement of puberty onset and gonadal steroid feedback.Conclusion: This review will briefly discuss on cellular and molecular level of kisspeptin, their potential effects on human and clinical application of kisspeptin on human reproductive disorder.Pulse Vol.8 January-December 2015 p.43-50